Comparison of three primer pairs included: novel primers IS711, universal primers B4 - B5 and 16SrRNA in the diagnosis of human brucellosis in suspected patients in Iran - H. Heidari, Pedram; Razavi, Mohammad Reza; Salehi, Mitra; Akhavan Sepahi, Abbas (Researcher Bulletin of Medical Sciences, 2021)
The genus Brucella is a worldwide distributed intracellular bacteria, which infects animals and human. Currently, this zoonosis has been diagnosed by microbiological and serological laboratory tests. Different PCR protocols with various primer pairs and different target genes have been published for the detection of Brucella, but only a few of these primers have been used in human samples. This study aimed to evaluate and compare the sensitivity and specificity of three primer pairs in the PCR technique, each of which separately amplifies three different regions in the Brucella genome, to determine which are more comfortable for the detecting of Brucella DNA in human clinical samples. 49 clinical serum samples were isolated from suspected patients in different cities in Iran from October 2017 to July 2018. The suspected patients with brucellosis-compatible symptoms were checked. These primers amplified 3 distinctive fragments in BCSP 31 gene (B4/B5), Designed IS711 primers, and a sequence of 16SrRNA of Brucella melitensis. The results showed that the B4/B5 primer pair had the highest sensitivity and specificity for the detection of both positive and negative samples (100%). The designed IS711 primer pair detected 94% of samples, whereas the 16SrRNA primer pair was the least sensitivity, being able to detect only 30.64% of samples. The specificity of 3 techniques was 100%. The B4/B5 primers were able to detect the smallest number of bacteria 0.05 CFU/reaction whereas IS711 was able to detect 2 CFU/reaction and 16SrRNA was able to detect 2×105 CFU/reaction.